2010
DOI: 10.1200/jco.2009.27.1932
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Versus Procarbazine, Lomustine, and Vincristine in Recurrent High-Grade Glioma

Abstract: Although TMZ (both arms combined) did not show a clear benefit compared with PCV, comparison of the TMZ schedules demonstrated that the 21-day schedule was inferior to the 5-day schedule in this setting. This challenges the current understanding of increasing TMZ dose-intensity by prolonged scheduling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 18 publications
3
146
0
3
Order By: Relevance
“…Somewhat better control rates at 6 months have been reported with a continuous dosing regimen of TMZ, 48 but not in recent phase II trial exploring a 21 out of 28 days schedule. 49 The BR12 trial which enrolled recurrent, TMZ-naïve malignant glioma patients provided no evidence for superiority of dose-intensified TMZ over standard-dosed TMZ, 50 but these data are of limited value in assessing the role of TMZ rechallenge for patients pre-exposed to TMZ. They do, however, suggest that there is no rationale for using dose-intensified TMZ in recurrent glioma patients who are TMZ-naive.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…Somewhat better control rates at 6 months have been reported with a continuous dosing regimen of TMZ, 48 but not in recent phase II trial exploring a 21 out of 28 days schedule. 49 The BR12 trial which enrolled recurrent, TMZ-naïve malignant glioma patients provided no evidence for superiority of dose-intensified TMZ over standard-dosed TMZ, 50 but these data are of limited value in assessing the role of TMZ rechallenge for patients pre-exposed to TMZ. They do, however, suggest that there is no rationale for using dose-intensified TMZ in recurrent glioma patients who are TMZ-naive.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…Beyond the randomized trial leading to the approval of TMZ mentioned above, two other randomized trials with TMZ monotherapy as one of the treatment arms have been published, a direct comparison with the combination of procarbazine, lomustine and vincristine (PCV) before TMZ became first-line standard [69] and a negative trial for the epidermal growth factor recetor (EGFR) tyrosine kinase inhibitor afatinib [70] ( Table 2 and The anti-vascular endothelial growth factor (VEGF) antibody bevacizumab [72][73][74][75], interferon-α2b [76], the multikinase inhibitor sorafenib [77], O6-benzylguanine [78], irinotecan [79], cisplatin [80,81], liposomal doxorubicine [82] and ABT-414, an EGFR-targeted antibody-drug conjugate conjugated to monomethylauristatin F [83].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%
“…A randomized trial comparing sdTMZ with procarbazine, in TMZ-naive patients, revealed a PFS6 of 21% versus 8%, with a median OS 1.5 months longer in the TMZ arm (127). Brada et al compared two different TMZ schedules with PCV, before TMZ became first-line standard, in patients with recurrent high-grade glioma (no separate data for GBM patients were provided) (166). In this trial, TMZ (both arms combined) did not display a clear benefit compared with PCV.…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 90%
“…Four randomized phase II clinical trials were conducted using single-agent TMZ (127,159,166,167). A randomized trial comparing sdTMZ with procarbazine, in TMZ-naive patients, revealed a PFS6 of 21% versus 8%, with a median OS 1.5 months longer in the TMZ arm (127).…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%